Accuracy of the smaller superior mesenteric vein sign for the detection of acute superior mesenteric artery occlusion. Issue 2 (28th September 2017) - Nakano, Takaaki; Ito, Toshitaka; Takei, Tetsuhiro; Takemoto, Masaaki
Abstract : Aims: The smaller superior mesenteric vein (SMV) sign is a well‐known computed tomography (CT) parameter for acute superior mesenteric artery (SMA) occlusion. This CT sign is potentially beneficial for the early diagnosis of acute SMA occlusion; however, few reports have documented this sign. The present study aimed to determine the accuracy of the smaller SMV sign for the detection of acute SMA occlusion. Methods: We retrospectively reviewed CT images from 20 patients with acute SMA occlusion and 1, 216 controls. We measured the external diameters of the SMV and SMA, and calculated the SMV/SMA diameter ratio. A ratio ≤1 indicated a positive smaller SMV sign. Results: Of the 20 patients, 14 had the smaller SMV sign, whereas of the 1, 216 controls, 88 had the smaller SMV sign. Of the 88 controls with a positive sign, 79 had apparent reasons for the decreased flow in the SMA and nine patients had no reason for the decreased flow. The sensitivity and specificity of the smaller SMV sign for acute SMA occlusion were 70% and 99.2%, respectively. Conclusion: The smaller SMV sign is an accurate and important CT parameter for the detection of acute SMA occlusion. Abstract : Smaller superior mesenteric vein sign on acute superior mesenteric artery occlusion.